Antioxidant Activity of Sweet Potato Based Tapai: Experimental Study on Different Varieties and Fermentation Duration (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Free radicals caused by modern living are linked to diseases like cancer, diabetes and heart disease. Antioxidants in food, such as sweet potatoes, are a safe way to prevent these. Sweet potatoes have lots of bioactive compounds, especially in the purple and yellow types. Fermentation, like in tapai made from sweet potatoes, can make antioxidants more active by changing phenolic compounds. The present study evaluated the antioxidant activity of different sweet potato types (purple, yellow, and white) at various fermentation durations. Sweet potatoes were fermented for 0, 2, 4 or 6 days and the antioxidant activity of the resulting tapai was measured using the DPPH method. The study found purple sweet potato tapai fermented for four days to have the highest antioxidant activity, with an IC₅₀ value of 52.7 µg/mL, almost reached vitamin C at IC₅₀ 45.6 µg/mL. Yellow and white sweet potato tapai showed much lower activity (IC₅₀ 68.4 and 83.1 µg/mL, respectively). The study showed antioxidant levels can vary depending on sweet potato variety and fermentation time. These findings contribute to the development of traditional fermented foods as a preventative dietary intervention against degenerative diseases, which are increasingly prevalent in modern society.